Kaplica Matki Bożej Uzdrowienia chorych w Galu na Wileńszczyźnie - Żurek, Waldemar Witold (Archiwa, Biblioteki i Muzea Kościelne, 2016)
In the Vilnius region near Troki there is the tiny village of Gaj situated in the forest; it is part of the parish of Stare Troki in the Archdiocese of Vilnius. The village is inhabited by dozens of residents who are Polish. In this village there is a chapel of Our Lady Health of the Sick, which was built in the thirties of the last century thanks to the efforts of Włodzimierz Andrzejewski’s brother (a member of the Brothers Hospitallers of Saint John of God) and his family. It was consecrated in 1937. The chapel houses a copy of the image of Our Lady Health of the Sick from the Holy Cross Church of the Brothers Hospitallers in Vilnius. To this day, on the last Sunday in August, the faithful gather in the parish fair to give thanks to God, through the intercession of Our Lady, for everything they received from Him.